2014
DOI: 10.1177/1040638714550183
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-induced damage to equine erythrocytes from exposure toPistacia atlantica, Pistacia terebinthus, andPistacia chinensis

Abstract: Two horses were referred for methemoglobinemia and hemolytic anemia following 5 acute deaths in their herd from an unidentified toxin source. Horses have a greater risk than other mammalian species of developing methemoglobinemia and hemolytic anemia following ingestion of oxidizing toxins, due to deficiencies in the mechanisms that protect against oxidative damage in erythrocytes. Their susceptibility to oxidative erythrocyte damage is evident in the numerous cases of red maple (Acer rubrum) toxicosis. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The affected horses had been observed to consume Pistacia leaves, which are known to contain gallic acid . In addition, in vitro testing performed using extract from Pistacia leaves and seeds, similar to that previously reported to confirm the oxidative and hemolytic properties of A. rubrum leaves, was consistent with oxidative and hemolytic effects on equine erythrocytes . The high liver iron concentration in all 3 necropsied horses is an expected finding with intravascular hemolysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The affected horses had been observed to consume Pistacia leaves, which are known to contain gallic acid . In addition, in vitro testing performed using extract from Pistacia leaves and seeds, similar to that previously reported to confirm the oxidative and hemolytic properties of A. rubrum leaves, was consistent with oxidative and hemolytic effects on equine erythrocytes . The high liver iron concentration in all 3 necropsied horses is an expected finding with intravascular hemolysis.…”
Section: Discussionsupporting
confidence: 86%
“…No maple trees, onions, or other plants associated with oxidant damage or hemolysis in horses were found. Two in vitro screening assays using a pyrogallol standard (0.17 mg/mL) as a positive control, confirmed the oxidative properties of P. atlantica , P. terebinthus , and P. chinensis leaf and seed extracts on equine erythrocytes; methemoglobin formation and hemolysis resulted after exposing equine erythrocytes to these plant extracts …”
Section: Case 1 and Casementioning
confidence: 69%
“…The ingestion of red maple leaves is known to cause oxidative damage to red blood cells causing severe hemolytic anemia in multiple species. 26 Gallic acid and tannic acid are believed to be the primary oxidants within red maple; however, pyrogallol, a metabolite of gallic acid, may also contribute to oxidant-induced damage. In vitro studies have shown that pyrogallol has a higher capacity to induce methemoglobin Al-Dissi in equine erythrocytes than tannic acid and gallic acid.…”
Section: Red Maple Toxicosismentioning
confidence: 99%
“…methemoglobin formation, alteration of aggregation, and reduction of cellular deformability (Baskurt and Meiselman, 1999). Therefore, the high susceptibility of equine erythrocytes to oxidant damage and the resulting hemorheologic alterations may have important consequences for tissue perfusion and cardiovascular adequacy in horses (Baskurt and Meiselman, 1999;Walter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of the heme iron in hemoglobin to the ferric (Fe 3+ ) state generates methemoglobin, which is incapable of transporting oxygen. Methemoglobin can be enzymatically reduced back to the functional ferrous (Fe 2+ ) state, primarily by nicotinamide adenine dinucleotide (NADH)-dependent methemoglobin reductase (Wright et al, 1999;Walter et al, 2014). Sulfhydryl groups in proteins and unsaturated lipids in erythrocyte membranes are especially susceptible to oxidation.…”
Section: Introductionmentioning
confidence: 99%